1998
DOI: 10.1159/000052706
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Genetic Diversity of Wild and Captive Groups of Microcebus murinus Using the Random Amplified Polymorphic DNA Method

Abstract: Continued survival of most animal species depends on population management and active protection. It is generally agreed that, in order to avoid extinction of endangered species, ex situ and in situ conservation must be developed in tandem. However, even though many recommendations have been put forward to promote the survival of captive populations, some rapidly become extinct due to loss of genetic diversity (drift effect). Genetic markers, such as random amplified polymorphic DNA (RAPD) markers, can be appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Average gene diversity across all loci (Nei, 1987) within Table 2. Analysis of molecular variance (AMOVA) for individuals from Emas National Park and Pantanal using Nei and Li (1979) (Cooper, 2000), carnivores (Ratnayeke et al, 2002), and primates (Neveu et al, 1998). Few studies using the RAPD technique have been reported on cervid species.…”
Section: Discussionmentioning
confidence: 99%
“…Average gene diversity across all loci (Nei, 1987) within Table 2. Analysis of molecular variance (AMOVA) for individuals from Emas National Park and Pantanal using Nei and Li (1979) (Cooper, 2000), carnivores (Ratnayeke et al, 2002), and primates (Neveu et al, 1998). Few studies using the RAPD technique have been reported on cervid species.…”
Section: Discussionmentioning
confidence: 99%
“…However, as noted above, drawbacks to this method (e.g., the extreme sensitivity of the procedure to PCR reaction conditions) have limited its application in studies of primate mating systems (Riedy et al, 1992), especially when compared with PCR-based microsatellite genotyping. Most recent applications of RAPD analysis in the primate literature involve estimating the degree of genetic variation within and between selected primate taxa (e.g., Lan et al, 1995;Neveu et al, 1998;Bachmann et al, 2000;Fausser et al, 2000;Ravaoarimanana et al, 2001) rather than as a tool for parentage analysis.…”
Section: Studies Of Mating Systems and Reproductive Strategiesmentioning
confidence: 99%
“…Methods for determining paternity [126] 14.4.2. Methods for assessing genetic variation; practical consequences [110,[127][128][129][130][131] 14.4.3. Genetic variation within existing populations of the species 14.4.4.…”
Section: Items For Husbandry Research 161mentioning
confidence: 99%